Next-generation optical storage area networks the light-trails approach. - Gumaste, Ashwin (IEEE Communications magazine)
Multiple architectures, technologies, and standards have been proposed for storage area networks, typically in the WAN environment. The transport aspect of storage signifies that optical communications is the key underlying technology. The contemporary SAN over optical network concept uses the optical layer for pure transport with minimal intelligence. This leads to high cost and overprovisioning. Future optical networks, however, can be expected to play a role in optimizing SAN extension into the WAN. An essential characteristic of SAN systems is tight coupling between nodes in a SAN network. Nodes in a SAN system have two critical functions that are presently emulated by data layers and can be offloaded to the optical layer. First, nodes need to signal among each other to achieve tasks such as synchronous and asynchronous storage. Second, to benefit from an optimized network, nodes need to allocate bandwidth dynamically in real time. In this article we show how the optical layer can be furthered from just pure transport to creating opportunities in provisioning as well as providing the mirroring function of SAN systems (multicasting) and consequently lead to reduction in cost. We demonstrate that the light-trail model is one way of efficiently utilizing the optical layer for SAN.